Measuring willingness to pay for freshness in perishable goods: An empirical analysis - Mariana Sousa; Sara Martins; Maria João Santos; Pedro Amorim; Winfried Steiner (Sustainability Analytics and Modeling)
Understanding consumer behavior toward perishable products is crucial for optimizing food supply chains, minimizing waste, and reducing lost sales. Such knowledge enables retailers to effectively incentivize the purchase of items nearing the end of their shelf life. Although some retailers apply markdowns to products with low remaining shelf life, limited empirical evidence exists on how these strategies affect consumer valuation and how perceptions evolve as products age. To address this gap, we investigate the effects of freshness, price, product attributes, and markdown labels on consumer purchasing decisions. Using discrete choice models estimated from revealed preference data provided by a major European retailer, we quantify consumers’ willingness to pay (WTP) for each additional day of shelf life across several perishable products, with a focus on the dairy category. Our findings reveal a non-linear relationship between remaining shelf life and WTP, alongside a statistically significant reduction in perceived value for products featuring markdown labels. Based on these findings, we recommend implementing differentiated markdown strategies targeted at specific products, coupled with transparent communication, to mitigate negative perceptions associated with discounted perishables. By improving how labeled products are perceived and strategically optimizing the timing and magnitude of markdowns, retailers can better align their strategies with consumer preferences, reduce waste, and improve profitability.